Al/Zn co-incorporated Cu–In–Se quantum dots for high efficiency quantum dot sensitized solar cells. (27th February 2020) - He, Fangfang; Wang, Wei; Xue, Weinan; Xie, Yiling; Zhou, Qianwen; Zhang, Jiachen; Li, Yan
Abstract : A facile method for synthesizing high-quality Cu–In–Se quantum dots (QDs) was developed by Al/Zn co-incorporation. Benefiting from the reduction of trap-state defects in QDs, the efficiency of solar cells basing prepared QDs is obviously improved. Abstract : Although Cu–In–Se (CISe) quantum dots (QDs) with narrow tunable bandgap and low toxicity have promising prospects in photovoltaics, their application is seriously restricted by high defect density. To develop a facile synthesis method for high-quality CISe QDs, Al and Zn ions were introduced into the synthesis of CISe QDs. Compared with the incorporation of Al or Zn alone, the trap-state defects in CISe QDs can be more effectively reduced by the co-incorporation of these metal ions. The synthesized CISe QDs then were used as light harvester materials to fabricate photoanodes for constructing quantum dot sensitized solar cells (QDSCs). The photovoltaic performance of the QDSCs based on Al/Zn co-incorporated QDs was observed to be much better than that of the QDSCs based on Al or Zn alone incorporated QDs, which could be ascribed to the suppression of unfavorable charge combination in QDSCs. A power conversion efficiency (PCE) of 10.27% ( J sc = 27.15 mA cm −2, V oc = 0.620 V, and FF = 61.0%) was achieved on the QDSCs with Cu2 S/brass counter electrodes and polysulfide electrolyte under simulated one full sun illumination, which is among the reported best PCEs of the QDSCs with a similar structure.